Phosphatidylcholine’s influence on Dysmenorrhea: conclusive insights from Mendelian randomization analysis - Li, Yuzheng; Zhou, Shiyao; Huang, Yuchen; Yu, Qiuhao; Wu, Qibiao (Frontiers in Genetics, 2024)
This study delves into the potential causal link between phosphatidylcholine (PC) levels and dysmenorrhea, utilizing genome-wide association study data and the TwoSampleMR approach. Our objective was to navigate beyond the confounding variables inherent in traditional observational research, aiming to furnish more dependable evidence of causality.Employing the method of Mendelian randomization, this study delved intothe purported causal relationships between serum lipid quantities and the incidence of menstrual discomfort.The analysis utilized single nucleotide polymorphisms (SNPs) closely related to lipid metrics as the instruments. To verify the resilience of our conclusions across diverse statistical methodologies, we undertook a battery of sensitivity tests,including MR-Egger and inverse variance weighting, to scrutinize our data for possiblepleiotropy and heterogeneity. The data revealed a tentative positive correlation betweenhigher phosphatidylcholine (PC) levels and an increased likelihood of dysmenorrhea, indicated by an odds ratio of 1.533 (95% confidence interval: 1.039 -2.262, P = 0.031).This association posits a potential new biomarker for the development of treatment modalities for dysmenorrhea. In conclusion, the discovery that increased phosphatidylcholine levels correlate with a greater risk of experiencing dysmenorrhea not only aids in assessing the likelihood of dysmenorrhea onset but also in guiding its diagnosis and prevention. Furthermore, this insight directs future research towards elucidating the biological underpinnings of dysmenorrhea.